2019
DOI: 10.1177/2292550319880913
|View full text |Cite
|
Sign up to set email alerts
|

Drainage Collection After Endoscopic-Assisted Transaxillary Dual-Plane Augmentation Mammaplasty Using Cold or Electrosurgical Separation of Interpectoral Space

Abstract: Background: Endoscopic transaxillary augmentation mammaplasty breast augmentation offers several advantages over other augmentation methods. Nonetheless, this procedure is fraught with some problems, including greater surgical trauma due to the longer separation area. We hypothesized that cold separation of the interpectoral space could reduce surgical injury in comparison to the electrosurgical method. This study aimed to compare the outcomes of endoscopic-assisted transaxillary augmentation mammaplasty using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Munhoz et al 9 reported a mean operative time of 55 minutes when performing transaxillary breast augmentation without endoscopic assistance via the blunt dissection approach. In contrast, previous studies 3,8,11,12 have shown that transaxillary breast augmentation with endoscopy requires approximately 100–120 minutes. In our study, the TET group required longer operative times than the NTET group (TET vs NTET: 133.60 ± 19.68 vs 113.13 ± 21.28 minutes), but the effect was not as drastic as we had anticipated; the reduction in time with the NTET procedure was only approximately 20 minutes.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Munhoz et al 9 reported a mean operative time of 55 minutes when performing transaxillary breast augmentation without endoscopic assistance via the blunt dissection approach. In contrast, previous studies 3,8,11,12 have shown that transaxillary breast augmentation with endoscopy requires approximately 100–120 minutes. In our study, the TET group required longer operative times than the NTET group (TET vs NTET: 133.60 ± 19.68 vs 113.13 ± 21.28 minutes), but the effect was not as drastic as we had anticipated; the reduction in time with the NTET procedure was only approximately 20 minutes.…”
Section: Discussionmentioning
confidence: 80%
“…The dwelling suction drainage was still applied to those patients of 2 groups. Most of plastic surgeons in China get used to using drains after breast augmentation 3 . It could be much safer for the surgeons to observe the bleeding post operation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations